Fatty acid profile and storage stability of loin muscle in response to dietary supplementation of Spirulina platensis in finishing crossbred pigs - Lakshmi, M; Ravi, A; Devasena, B; Shakeela, S; Reddy, G V Bhaskara (Journal of Meat Science, 2024)
The study was conducted to study whether feeding Spirulina platensis hasbeneficial effect on enhancing the fatty acid profile and storage stabilityof the loin muscle of pigs. A total of 24 male finishing pigs (Large WhiteYorkshire X Desi) were housed individually and distributed randomly intofour equal groups with six animals in each group. Four isonitrogenousexperimental diets (T1 to T4) were formulated by including dry Spirulinaplatensis at 0, 0.5, 1.0 and 1.5 %, respectively and fed during finishingphase (50 to 75 kg) live weight. Dietary treatments had no significant(P>0.05) effect on the total lipid and total cholesterol content of theloin muscle of pigs. The level of polyunsaturated fatty acids (PUFA) washigher (P
Keywords: Loin muscle; Spirulina; Fatty acid profile; Storage stability; Sensory evaluation